European S1 guideline for the treatment of hidradenitis suppurativa/acne inversa. (30th January 2015) - Zouboulis, C.C.; Desai, N.; Emtestam, L.; Hunger, R.E.; Ioannides, D.; Juhász, I.; Lapins, J.; Matusiak, L.; Prens, E.P.; Revuz, J.; Schneider‐Burrus, S.; Szepietowski, J.C.; et al.
Abstract: Hidradenitis suppurativa/acne inversa (HS) is a chronic, inflammatory, recurrent, debilitating skin disease of the hair follicle that usually presents after puberty with painful, deep‐seated, inflamed lesions in the apocrine gland‐bearing areas of the body, most commonly the axillae, inguinal and anogenital regions. A mean disease incidence of 6.0 per 100 000 person‐years and an average prevalence of 1% has been reported in Europe. HS has the highest impact on patients' quality of life among all assessed dermatological diseases. HS is associated with a variety of concomitant and secondary diseases, such as obesity, metabolic syndrome, inflammatory bowel disease, e.g. Crohn's disease, spondyloarthropathy, follicular occlusion syndrome and other hyperergic diseases. The central pathogenic event in HS is believed to be the occlusion of the upper part of the hair follicle leading to a perifollicular lympho‐histiocytic inflammation. A highly significant association between the prevalence of HS and current smoking (Odds ratio 12.55) and overweight (Odds ratio 1.1 for each body mass index unit) has been documented. The European S1 HS guideline suggests that the disease should be treated based on its individual subjective impact and objective severity. Locally recurring lesions can be treated by classical surgery or LASER techniques, whereas medical treatment either as monotherapy or in combination with radical surgery is more appropriate for widely spread lesions. Medical therapy may include antibiotics (clindamycin plus rifampicine, tetracyclines), acitretin and biologics (adalimumab, infliximab). A Hurley severity grade‐relevant treatment of HS is recommended by the expert group following a treatment algorithm. Adjuvant measurements, such as pain management, treatment of superinfections, weight loss and tobacco abstinence have to be considered.